Caracterização sociodemográfica, psicossocial e clínica de usuários de substâncias psicoativas atendidos em centro de atenção psicossocial álcool e drogas (CAPSad) - Costa, Janelise Bergamaschi Paziani (2012)
Introduction: The use/consumption of psychoactive substances is considered a complex phenomenon, which has biological, psychological and social origins and consequences. Objectives: Describing, analyzing and comparing socio-demographic, psychological and clinical characteristics presented by a population having a Substance Use Disorder. Casuistic and Method: A convenience sample comprising 50 adult male patients who took part in the present study were seen in a Psychosocial Attention Center Alcohol and Drugs (CAPSad) based in a medium-sized city located in São Paulo State countryside. An Identification Form containing personal and socio-demographic features, as well as a Semi-directed Interview Script, were used for people with alcohol and/or drug-related problems. Data were analyzed by means of non-parametric statistic evidences and qualitative analysis of frequency and percentage of answer category having the same semantic meaning. Results: The study group mostly comprised an adult (28-37 and 48-58 years old), negroid (62%), not engaged (72%), evangelic (44%), unemployed (59,18%) population born in areas around the target city (44,68%), with 5 to 8 years of study (42%) and a monthly family income of 3-5 minimum salaries (47,73%). 68% of these patients had been under treatment for at most a month, especially the youngest interviewed ones (18-37 years old). There has been balance between the participants directed to CAPSad and the ones who have searched for help on their own. Some of the main reasons for this search were: willingness to quit consuming, psychological and emotional problems, as well as chemical addiction. 43,18% of the patient sample were abused (esp. physically) in childhood and/or adolescence, and 74% reported having family problems involving alcohol and/or others drugs. Psychoactive substances use was a contributing factor to damages in the quality of relationship with family of origin, spouse and children. Participants reported significant changes and social repertoire and part of leisure activities was associated to the very use of substances or related activities. 76,60% declared having friends who made use of alcohol and/or other drugs. Alcohol (98%), nicotine (84%), cocaine (72%) and cannabis (72%) derivates, inhalants (48%), hallucinogens (22%) and psychotropic medicine (12%) were the most commonly consumed drugs in a lifetime found among patients. Marijuana, cocaine and crack were statistically associated to research youngest population. 64% started using substances in adolescence, mainly due to friendship, party attendance and curiosity and 38% of these youngsters already made continuous use of them in this very life stage. 66% indicated ‗group, friendship circle, friends as usage partners, 72,92% declared uninterrupted use of drugs for some days and 86% of them reported having had periods without any drug contact. The main factors encountered to relapse were loneliness, family distance, belief of being able to drink with no negative consequences, as well as of feeling fine, use willingness and pleasure and individual psychological characteristics. The most common treatments for problems with alcohol and/or other drugs were CAPSad, Hospitalization, Emergency Room, ―Alcoólicos Anônimos‖, ―Narcóticos Anônimos‖, ―Amor Exigente‖ and religion. Participants reported psychological (96%), physical (90%) and cognitive (71,92%) damages related to substance use. Conclusions: It has been observed that a great percentage of the total number of adult participants in the present study presented significant damages related to alcohol and other drugs abuse/dependence, compromising all individual s functioning areas. Although the results are not conclusive to predicting factors in childhood to drug use, considering sample characteristics varied from worse to better socioeconomics and life conditions. In adolescence, individuals with significant damages, changes and sufferings, in touch with user friends and presenting common features for abuse maintenance were predominant. We may conclude that efficient health promoting and prevention programs and more effective treatments and rehabilitation programs must take into consideration users population heterogeneity.